Enhancing sustainable agricultural export performance through digitalization: The distinct roles of domestic and foreign inputs - Weifeng Huang; Yan Huang (PLoS ONE, 2025)
Amid the restructuring of global value chains (GVC), digital transformation has become a vital strategy for enhancing agricultural export performance and strengthening international competitiveness, while also contributing to the United Nations Sustainable Development Goals, particularly the reduction of poverty and hunger. This study utilizes the OECD Activity of Multinational Enterprises (AMNE) database and employs a two-way fixed effects model to assess the impact of agricultural digitalization inputs on export performance, measured by gross exports (E), domestic value-added in exports (DVA), and the ratio of domestic value-added in exports to gross exports (EDVAR). The results indicate that both domestic and foreign digitalization inputs significantly enhance export performance, with domestic inputs exerting a stronger effect. The heterogeneity analysis reveals that domestic inputs have a more significant impact in developing countries. Mechanism tests suggest that domestic inputs enhance production efficiency, whereas foreign inputs primarily reduce trade costs. Policy recommendations include promoting digital innovation, enhancing self-reliance and resilience, optimizing the digital trade environment, and securing adequate human capital, land, and institutional support.